2022
DOI: 10.18063/msam.v1i2.9
|View full text |Cite
|
Sign up to set email alerts
|

Flexural behavior of 3D printed bio-inspired interlocking suture structures 

Abstract: Additive manufacturing has allowed producing various complex structures inspired by natural materials. In this research, the bio-inspired suture structure was 3D printed using the fused deposition modeling printing technique to study its bending response behavior. Suture is one of the most commonly found structures in biological bodies. The primary purpose of this structure in nature is to improve flexibility by absorbing energy without causing permeant damage to the biological structure. An interesting discov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In MEX, the thermoplastic material is melted and extruded from a hot end to form a printed layer to produce the desired object [ 40 , 41 ]. Alsoufi et al [ 42 ] reported that the shape error of PLA was within 3.00% on each side of a 40 mm (L) × 40 mm (W) × 15 mm (H) specimen, which is excellent accuracy for PLA fabricated by MEX.…”
Section: Discussionmentioning
confidence: 99%
“…In MEX, the thermoplastic material is melted and extruded from a hot end to form a printed layer to produce the desired object [ 40 , 41 ]. Alsoufi et al [ 42 ] reported that the shape error of PLA was within 3.00% on each side of a 40 mm (L) × 40 mm (W) × 15 mm (H) specimen, which is excellent accuracy for PLA fabricated by MEX.…”
Section: Discussionmentioning
confidence: 99%
“…The machine was located in an industrial hall to prevent significant temperature changes (operation at room temperature), depending on the time of day and night. Referring to the 3D printing characterization found in [42,43], the most important process parameters considered in the current study are as follows: first, it should be noted that the slicer CURA 4.4.0, executed for its standard MEX technology settings regarding extrusion nozzle diameter, number of perimeter layers, and layer thickness, was used to generate G-code. Specifically, the gears were printed using a 0.4 mm nozzle diameter, with a 0.3 mm layer thickness, three outline perimeters, and a 100% infill density with the application of a linear pattern.…”
Section: Methodsmentioning
confidence: 99%
“…This sets the basis for designing structures that are currently almost infeasible to produce with traditional manufacturing, for example seamless rings or structures with varying yarn geometry. Further, AM introduces the ability for production on demand, increases design flexibility and shortens the supply chain [6,17,22,23].…”
Section: Introductionmentioning
confidence: 99%